Enhancing Early Childhood Vocabulary Development through Paper-Book-Based Storytelling in EFL Classrooms - Fahriany Fahriany (Jurnal DinamikA, 2026)
This study examines the role of paper-book-based storytelling in supporting teachers’ teaching of English vocabulary to early childhood learners. The research focuses on the classroom implementation of storytelling activities, participants’ perceptions, and the pedagogical effects on young learners’ language development. The study was conducted in a kindergarten setting with one English teacher and eleven five-year-old students. Using a qualitative descriptive research design, data collection involved in-class observations along with semi-structured teacher interviews, and documentation of instructional activities and students’ learning products. The data collected were analyzed thematically to identify recurring patterns related to instructional practices, learner responses, and learning outcomes. Through repeated exposure to vocabulary embedded in meaningful narrative contexts, children demonstrated improved understanding of word meanings and extensive confidence in using new vocabulary during classroom interactions. The use of interactive and multimodal storytelling techniques such as gestures, visual illustrations, questioning, and student participation was found to sustain learners’ attention and promote active engagement. In addition, the study highlights the teacher’s intentional instructional strategies in selecting age-appropriate stories, scaffolding vocabulary learning, and encouraging student participation. While the approach proved pedagogically beneficial, the study also identifies practical challenges, including limited instructional time and the need for teacher creativity in managing classroom dynamics. The findings indicate that paper-book-based storytelling is an engaging, reachable, and culturally meaningful method for teaching vocabulary in early childhood education.